PROPOSED MODULE IN TEACHING PRACTICAL RESEARCH 1 - P. Zita, Mark Kevin P. Zita (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
The study summarizes the focus on the challenges faced by senior high school teachers in teaching Practical Research 1, their instructional strategies, and the proposed self-instructional module. It revealed the challenges encountered by teachers, such as their insufficient knowledge and experience in research, difficulties in guiding students through research paper writing due to limited resources, and the necessity for online learning resources. Instructional strategies employed by teachers primarily involved the use of textbooks and modules, complemented by online resources, presentations, and gadgets for teaching purposes. Most teachers believed these strategies to be appropriate, enhancing student interest and learning. Teachers identified the need for a wider variety of sample research materials, detailed procedures for research, video lessons, and discussions as essential components in teaching Practical Research 1. They also recommended research guidebooks, school-owned websites, and additional training for teachers handling the subject. The study's key takeaways included the significance of comprehensive resources for teaching research effectively, the value of diverse instructional materials, and the proposal for a self-instructional module to facilitate independent learning in Practical Research 1. Overall, the research highlighted the pressing needs of teachers for enhanced resources, strategies, and a comprehensive self-instructional module to effectively teach Practical Research 1 in senior high school.